Effects of cold plasma, gamma and e-beam irradiations on reduction of fungal colony forming unit levels in medical cannabis inflorescences - Shachar Jerushalmi; Marcel Maymon; Aviv Dombrovsky; Stanley Freeman (BMC, 2020)
Abstract Background The use of medical cannabis (MC) in the medical field has been expanding over the last decade, as more therapeutic beneficial properties of MC are discovered, ranging from general analgesics to anti-inflammatory and anti-bacterial treatments. Together with the intensified utilization of MC, concerns regarding the safety of usage, especially in immunocompromised patients, have arisen. Similar to other plants, MC may be infected by fungal plant pathogens (molds) that sporulate in the tissues while other fungal spores (nonpathogenic) may be present at high concentrations in MC inflorescences, causing a health hazard when inhaled. Since MC is not grown under sterile conditions, it is crucial to evaluate current available methods for reduction of molds in inflorescences that will not damage the active compounds. Three different sterilization methods of inflorescences were examined in this research; gamma irradiation, beta irradiation (e-beam) and cold plasma to determine their efficacy in reduction of fungal colony forming units (CFUs) in vivo. Methods The examined methods were evaluated for decontamination of both uninoculated and artificially inoculated Botrytis cinerea MC inflorescences, by assessing total yeast and mold (TYM) CFU levels per g plant tissue. In addition, e-beam treatment was also tested on naturally infected commercial MC inflorescences. Results All tested methods significantly reduced TYM CFUs at the tested dosages. Gamma irradiation reduced CFU levels by approximately 6- and 4.5-log fold, in uninoculated and artificially inoculated B. cinerea MC inflorescences, respectively. The effective dosage for elimination of 50% (ED50)TYM CFU of uninoculated MC inflorescence treated with e-beam was calculated as 3.6 KGy. In naturally infected commercial MC inflorescences, e-beam treatments reduced TYM CFU levels by approximately 5-log-fold. A 10 min exposure to cold plasma treatment resulted in 5-log-fold reduction in TYM CFU levels in both uninoculated and artificially inoculated B. cinerea MC inflorescences. Conclusions Although gamma irradiation was very effective in reducing TYM CFU levels, it is the most expensive and complicated method for MC sterilization. Both e-beam and cold plasma treatments have greater potential since they are cheaper and simpler to apply, and are equally effective for MC sterilization.